Inhibitory Effects of Antimicrobial Peptides on Lipopolysaccharide-Induced Inflammation - Yue Sun; Dejing Shang (Hindawi Limited, 2015)
Antimicrobial peptides (AMPs) are usually small molecule peptides, which display broad-spectrum antimicrobial activity, high efficiency, and stability. For the multiple-antibiotic-resistant strains, AMPs play a significant role in the development of novel antibiotics because of their broad-spectrum antimicrobial activities and specific antimicrobial mechanism. Besides broad-spectrum antibacterial activity, AMPs also have anti-inflammatory activity. The neutralization of lipopolysaccharides (LPS) plays a key role in anti-inflammatory action of AMPs. On the one hand, AMPs can readily penetrate the cell wall barrier by neutralizing LPS to remove Gram-negative bacteria that can lead to infection. On the contrary, AMPs can also inhibit the production of biological inflammatory cytokines to reduce the inflammatory response through neutralizing circulating LPS. In addition, AMPs also modulate the host immune system by chemotaxis of leukocytes, to promote immune cell proliferation, epithelialization, and angiogenesis and thus play a protective role. This review summarizes some recent researches about anti-inflammatory AMPs, with a focus on the interaction of AMPs and LPS on the past decade.